Cover Picture: Gold‐Catalyzed Aminoalkenylation of β‐Amino‐1, n‐Diynols to Cycloalkyl‐, Piperidinyl‐ and Pyranyl‐Fused Pyrroles (Adv. Synth. Catal. 9/2016). Issue 9 (3rd May 2016) - Kothandaraman, Prasath; Zhao, Yichao; Lee, Bo Ra; Le Ng, Clarrisa Jia; Lee, Jun Yi; Ayers, Benjamin James; Chan, Philip Wai Hong
Abstract : More than just a pretty face. The inside front cover picture, provided by Chan and co‐workers, illustrates how Ph3 PAuNTf2 can be made to work hard. A catalytic amount of the Group 11 complex was demonstrated to mediate the facile and chemoselective aminoalkenylation of β ‐ amino‐1, n ‐diynols to cycloalkyl‐, piperidinyl‐ and pyranyl‐fused pyrroles in good to excellent yields. Details can be found in the communication on pages1385–1391 (P. Kothandaraman, Y. Zhao, B. R. Lee, C. J. L. Ng, J. Y. Lee, B. J. Ayers, P. W. H. Chan, Adv. Synth. Catal. 2016, 358, 1385–1391; DOI:10.1002/adsc.201600011 ).